Stable paretian distributions: an unconditional model for PSI20, DAX and DJIA indexes - Curto, J.; Reis, E.; Esperança, J. P. (Revista de Mercados e Activos Financeiros, 2003)
The family of stable distributions is usually regarded as an appropriate probability model for stock returns because of their theoretical properties: only stable distributions have domains of attraction and a stable distribution belongs to its own domain of attraction; and it was empirically observed that stock returns distributions display fatter tails than the normal distribution. In this empirical study we test the returns of Portuguese, German and US stock indexes’ conformity to stable Paretian distributions with characteristic exponent bellow 2, by comparison with the normal distribution, which is also stable Paretian but with a characteristic exponent equal to 2.